Spectrally Tuned Lanthanide Photoluminescence for Point-of-Care Testing - Valta, Timo (fi=Turun yliopisto|en=University of Turku|, 2015)
Point-of-care (POC) –diagnostics is a field with rapidly growing market share. As these applications become more widely used, there is an increasing pressure to improve their performance to match the one of a central laboratory tests. Lanthanide luminescence has been widely utilized in diagnostics because of the numerous advantages gained by the utilization of time-resolved or anti-Stokes detection. So far the use of lanthanide labels in POC has been scarce due to limitations set by the instrumentation required for their detection and the shortcomings, e.g. low brightness, of these labels. Along with the advances in the research of lanthanide luminescence, and in the field of semiconductors, these materials are becoming a feasible alternative for the signal generation also in the future POC assays. The aim of this thesis was to explore ways of utilizing time-resolved detection or anti-Stokes detection in POC applications. The long-lived fluorescence for the time-resolved measurement can be produced with lanthanide chelates. The ultraviolet (UV) excitation required by these chelates is cumbersome to produce with POC compatible fluorescence readers. In this thesis the use of a novel light-harvesting ligand was studied. This molecule can be used to excite Eu(III)-ions at wavelengths extending up to visible part of the spectrum. An enhancement solution based on this ligand showed a good performance in a proof-of-concept -bioaffinity assay and produced a bright signal upon 365 nm excitation thanks to the high molar absorptivity of the chelate. These features are crucial when developing miniaturized readers for the time-resolved detection of fluorescence. Upconverting phosphors (UCPs) were studied as an internal light source in glucose-sensing dry chemistry test strips and ways of utilizing their various emission wavelengths and near-infrared excitation were explored. The use of nanosized NaYF :Yb3+,Tm3+-particles enabled the replacement of an external UV-light source with a NIR-laser and gave an additional degree of freedom in the optical setup of the detector instrument. The new method enabled a blood glucose measurement with results comparable to a current standard method of measuring reflectance. Microsized visible emitting UCPs were used in a similar manner, but with a broad absorbing indicator compound filtering the excitation and emission wavelengths of the UCP. This approach resulted in a novel way of benefitting from the non-linear relationship between the excitation power and emission intensity of the UCPs, and enabled the amplification of the signal response from the indicator dye.

Vieritestaus on nopeasti laajeneva diagnostiikan osa-alue. Näiden sovellusten yleistyminen asettaa myös vaatimuksia niiden suorituskyvylle, jonka tulisi ideaalitapauksessa yltää keskuslaboratoriotestien tasolle. Lantanidien luminesenssia on jo pitkään hyödynnetty diagnostisissa sovelluksissa johtuen niiden lukuisista eduista, joita saavutetaan käytettäessä aikaerotteista tai käänteisviritykseen perustuvaa mittaustekniikkaa. Tähän asti lantanidileimojen käyttö vieritestauksessa on kuitenkin ollut vähäistä, johtuen niiden havainnointiin käytettyjen laitteistojen ja itse leimojen rajoituksista. Näissä tapahtuneen kehityksen myötä lantanidileimat ovat jo varteenotettava vaihtoehto entistä parempien vieritestien kehitykseen. Tämän väitöstyön tavoitteena oli tutkia tapoja hyödyntää aikaerotteista ja käänteisviritysmittaustapaa vieritestauksessa. Aikaerotteisen mittauksen vaatima pitkäikäinen fluoresenssi voidaan tuottaa lantanidikelaateilla, joiden viritys tapahtuu perinteisesti ultraviolettiaallonpituuksilla. Tämän virityksen tuotto on kuitenkin hankalaa vieritestaukseen soveltuvalla mittalaitteella. Tässä väitöstyössä tutkittiin uuden ligandin käyttöä Eu(III)-ionin virityksessä. Tutkitun ligandin viritysspektri ylsi näkyvän valon aallonpituuksille ja soveltui käytettäväksi bioaffiniteettimäärityksessä. Uusi kehitysliuos toimi hyvin mallina käytetyssä bioaffiniteettimäärityksessä ja tuotti voimakkaan signaalin 365 nm virityksellä johtuen kelaatin suuresta molaarisesta absorptiviteetista. Nämä ominaisuudet ovat keskeisiä, kun kehitetään vieritestaukseen soveltuvia, pienikokoisia mittalaitteita aikaerotteisen fluoresenssin mittaukseen. Käänteisviritteisiä partikkeleita puolestaan käytettiin sisäisinä valonlähteinä veren glukoosipitoisuutta mittaavissa testiliuskoissa, hyödyntäen näiden partikkelien lähi-infrapunaviritystä ja lukuisia emissioaallonpituuksia. Nanokokoisten NaYF :Yb3+,Tm3+-partikkeleiden käyttö mahdollisti ulkoisen ultraviolettivalonlähteen korvaamisen lähi-infrapunalaserilla ja mittalaitteen optisen kokoonpanon vapaamman suunnittelun. Uusi mittaustapa tuotti tuloksiltaan standardimenetelmään verrattavan suorituskyvyn. Mikrokokoisia, näkyvän valon aallonpituuksilla emittoivia käänteisviritteisiä partikkeleita hyödynnettiin vastaavalla tavalla, mutta käyttäen laajalla aallonpituusalueella absorboivaa indikaattoriyhdistettä, suodattaen sekä partikkelien emissio- että viritysaallonpituuksia. Tämä menetelmä mahdollisti uuden tavan hyödyntää näiden partikkelien viritys- ja emissiotehon välistä epälineaarista suhdetta ja mahdollisti indikaattoriyhdisteen tuottaman signaalin vahvistamisen.